Implementation of the Anti-Anemia Student Program (Mahamia) in Classes of Pregnant Women - Ryka Juaeriah; Dyeri Susanti (Jurnal Kebidanan, 2023)
The prevalence of anemia among pregnant women based on WHO data is still quite high at 41.8%. Anemia has a bad effect on the mother, both in terms of pregnancy, childbirth, and postpartum, namely abortion, premature, low birth weight, prolonged labor, postpartum hemorrhage, shock, intrapartum and postpartum infection, and can even cause maternal death. Adherence to consuming Fe tablets was measured by the accuracy of the amount, method, and frequency of consumption per day. The non-compliance of pregnant women taking Fe tablets can have a greater chance of developing anemia. The Class Program for Pregnant Women (KIH) is a means to learn together about health for mothers in groups that aim to increase knowledge and skills about pregnancy, pregnancy care, understanding, attitudes, and behavior of pregnant women in nutritional management, including giving Fe tablets to control anemia. Midwifery students as prospective health workers must have competence in providing midwifery care for pregnant women, one of the competencies is handling anemia and pregnant women. The purpose of this study was to determine the increase in Hb in pregnant women through the Anti-Anemia Student Program (Mahamia) through KIH. This study used a true experimental design with a pre-posttest control group design. The research was conducted in the working area of Public Health Center Leuwigajah Cimahi, with purposive sampling, the number of intervention groups was 20 respondents and the control group was 20 respondents. The research analysis used a paired t-test with the result that there was an increase in the mean Hb in the intervention group before and after treatment was 9.075 to 11.180 with an ap value of 0. 000 (p> 0.05), and there was an increase in the mean Hb in the control group before and after treatment, 10.150 to 11.016 with an ap value of 0.000 (p> 0.05). From the research results, it is hoped that the Mahamia Program through KIH can increase Hb levels in pregnant women who are anemic.